The use of pasung media to improve collaboration and learning outcomes food chains class V SDN Mojorejo 1 Batu - Cholifah , Nur Henny; Husamah; Nafi’a , Toyyibah Wijaya (JURNAL PENDIDIKAN DASAR NUSANTARA, 2023)
This Classroom Action Research aimed to find out the application of PASUNG media (connecting boards) to improve collaboration and learning outcomes for fifth-grade students at SDN Mojorejo 1 Batu City. The research method used was the classroom action research method. The subjects of this study were fifth-grade students at SDN Mojorejo 1 Batu City. Data on collaboration and learning outcomes were obtained from evaluation test results and student group activities through collaboration observation sheets. Based on the data obtained, learning using PASUNG media (connecting boards) can improve collaboration and student learning outcomes which can be seen from the results of student products in the form of miniature food chains. The results of student collaboration from Cycle I increased from 75% to 81% in Cycle II. Meanwhile, the average learning outcomes data of students in Cycle I was 73%, which increased to 85% in Cycle II. Based on the learning activities using PASUNG (Papan Sambung) media and creating a mini food chain project by the students, it can be concluded that the collaboration and learning outcomes of the students improved.